Strategi Penangan Permukiman di Kabupaten Jeneponto: studi Kasus: Permukiman Kumuh di Kawasan Allu Kecamatan Bangkala - Rukni Rahayu; Syafri Syafri; Emil Salim Rasyidi; Jamilah Abbas (Journal of Urban Planning Studies, 2022)
The purpose of this study was to analyze the level of slums, determine the determinant factors and formulate strategies for preventing and improving the quality of settlements in the Allu area, Bangkala district, and Jeneponto district. This type of research is mixed method research. To analyze the level of slums in the Allu Area, Bangkala District, Jeneponto Regency using baseline scoring analysis, to determine the determinant factors that cause the level of slums, Multiple Linear Regression analysis is used and to determine the effect of the slum level. The main conclusion of this study is that based on the results of the baseline scoring analysis, it shows that the level of slums in the Allu Area, Bangkala District, and Jeneponto Regency is in the medium slum category. To find out the determinant factors that cause the level of slums in the Allu area are the condition of buildings, conditions of drinking water supply, environmental drainage conditions, wastewater treatment conditions, waste management conditions, fire protection, and land ownership status. The macro concept of handling slum areas in the allu area is prevention, restoration, and rejuvenation of the area.